The Role of Islamic Religious Education in Children's Mental Health (Reflection of Daradjat Zakiah Thoughts) - Rianawati, (International Journal of Psychosocial Rehabilitation, 2020)
Religion leads human life in good direction through various obligatory rules that must be obeyed. There are rules that must be obeyed to be carried out, those that are obligatory, sunnah or permissible. There are rules to be abandoned, either by illicit or makruh laws. The purpose of the rules in religion is for the good and benefit also to avoid human bad sides or depletion of himself. If humans live according to the teachings of religion, then he will get the happiness of the world and the hereafter. And vice versa also when humans do not heed or ignore the teachings of Islam, his life is not happy both the world and the hereafter. Humans who have faith and are devoted to Allah SWT and surrender only to Allah SWT will cause a feeling of happiness, calm and peace and also mentally healthy. Humans who are mentally healthy then he can live his life optimistically, hoping for a variety of goodness only to Allah, patient and calm when he has a disaster or problems, can adjust himself to the environment because of human obligations to foster good social relations, both to parents, relatives, family, neighbors and the wider community. Through Islamic religious education, children know, understand, appreciate, believe and fear Allah Almighty to obtain a healthy mentality. This study reveals to reflect the thoughts of Zakiah Daradjat in the concept of Islamic education on children's mental health and the relationship between Islamic education and mental health. This research is also a critical reflection activity that is in the area of interpreting the thoughts of a character. Therefore, the method used to conduct the research process must be a familiar method and can be a place for the researcher to study the research theme. The work process in this research consists of reading activities, interpreting activities, all of which the researcher directs to reveal relevant realities and phenomena at present, in Indonesia by using the results of interpretation of text phenomena from the concepts of zakiah daradjat thought. The purpose of this study is to describe Zakiah Daradjad's thoughts about: 1) The concept of mental health. 2) The role of religion in mental health 3) The concept of Islamic education, 4) The role of Islamic education in children's mental health.